2021
DOI: 10.3390/microorganisms9112293
|View full text |Cite
|
Sign up to set email alerts
|

A Low to Medium-Shear Extruded Kibble with Greater Resistant Starch Increased Fecal Oligosaccharides, Butyric Acid, and Other Saccharolytic Fermentation By-Products in Dogs

Abstract: The objective of this study was to assess whether diets with increased resistant starch (RS) had a positive effect on markers of colonic health in dogs. Three identical diets were extruded with high, medium and low shear (HS, MS and LS) to incrementally increase RS, and fed to 24 dogs in a replicated 3 × 3 William’s Latin square design for 28-day periods. Fasting blood and fresh feces were collected on the last week of each period. Fecal quality was maintained among treatments. Gut integrity markers were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…Gelatinized starch provides functionality to the food, making it more accessible for digestion by mammalian enzymes. In contrast, a portion of the ungelatinized starch resists digestion at the SI (RS type 2) and promotes health benefits as a prebiotic in the large intestine ( Peixoto et al, 2018 ; Ribeiro et al, 2019 ; Jackson et al, 2020 ; Corsato Alvarenga et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gelatinized starch provides functionality to the food, making it more accessible for digestion by mammalian enzymes. In contrast, a portion of the ungelatinized starch resists digestion at the SI (RS type 2) and promotes health benefits as a prebiotic in the large intestine ( Peixoto et al, 2018 ; Ribeiro et al, 2019 ; Jackson et al, 2020 ; Corsato Alvarenga et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, in vitro RS did not correlate with in vivo ileal starch digestibility of dogs ( Murray et al, 1999 ). However, a recent study using a corn recipe produced via extrusion at three levels of thermomechanical energy found that minimal changes in RS measured using the same in vitro protocol ( McCleary et al, 2002 ) were sufficient to positively impact markers of gut health ( Corsato Alvarenga et al, 2021c ). We expected similar findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations